Management of Patients with Gastrointestinal Stromal Tumor (GIST) : Serial Case Report - Munir, Sirajul; Ompusunggu, Mangalindung; Suprapto, Bambang (Jurnal Kedokteran Mulawarman, 2024)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract. These are rare representing approximately 0.1-3% of all GI. The management of GIST is carried out using a multidisciplinary approach. Standard treatment of localized GIST is complete surgical resection associated (or not) with adjuvant Imatinib therapy. We reported 4 cases of GISTs with different management. We performed the surgical excision in three female patients with a median age of 44.7 years and 1 male patient get neoadjuvant imatinib due to unresectable mass. In our series, clinical manifestations are variable among patients, abdominal discomfort is the most primary symptoms. All of our patients received one year of Imatinib 400 mg daily therapy after the surgery and follow up based on Algorithm Treatment For GISTs.